A few remarks on the Inedita Pseudo-Chrysostomic Homily De transfiguratione et eleemosyna (CPG 5009; BHGn 1996t) - Gârbacea, Radu (HTS teologiese studies, 2021)
The article presents the preliminary results of the author’s study of the unedited homily De transfiguratione et eleemosyna (CPG 5009; BHGn 1996t), ascribed to John Chrysostom. The question of the manuscript tradition is first discussed. The article shows that Maurice Sachot is right when he indicates only the manuscript Romanus Angelicus gr. 125 (T.1.7) as a manuscript witness of this homily and that the other two witnesses indicated by Pinakes are erroneous. Then, the descriptions of the folios that preserve the homily are analysed in the light of a new examination of them. This re-examination shows that hitherto several sources that inspired the compiler have gone unnoticed. This is followed by a brief summary of the contents of the homily and an analysis of the passages in which almsgiving is mentioned.Contribution: The article offers a re-examination of the folios 353v–361 from the manuscript Romanus Angelicus gr. 125 (T.1.7), the first presentation of the content of the homily De transfiguratione et eleemosyna, and tries to shed light on the association of the theme of the Transfiguration with almsgiving.